Constraints on the Exercise of Contractual Powers - Kós, J Stephen (Victoria University of Wellington Law Review, 2022)
This article considers a topic largely ignored by the standard contract texts: contractual powers vested, usually without express restraints, in one of the contracting parties. It gathers the leading Commonwealth decisions on the subject and considers the nature and limits of the commonly-implied "default rule" that such powers may not be exercised arbitrarily, unreasonably or for an improper purpose. The author concludes that in the case of substantive principles such as error of law, improper purpose and irrationality, there is no fundamental difference between the interests protected by contract law, trust law and public law – and nor is there any fundamental difference between the tools used by each to provide that protection.